Knowledge, Attitudes, and Self-efficacy as Predictors of Preparedness for Oncology Clinical Trials: A Mediational Model. (May 2014) - Manne, Sharon; Kashy, Deborah; Albrecht, Terrance; Wong, Yu-Ning; Flamm, Anne Lederman; Benson, Al B.; Miller, Suzanne M.; Fleisher, Linda; Buzaglo, Joanne; Roach, Nancy; Katz, Michael; Ross, Eric; et al.
Objective. This study used the Ottawa Decision Support Framework to evaluate a model examining associations between clinical trial knowledge, attitudinal barriers to participating in clinical trials, clinical trial self-efficacy, and clinical trial preparedness among 1256 cancer patients seen for their first outpatient consultation at a cancer center. As an exploratory aim, moderator effects for gender, race/ethnicity, education, and metastatic status on associations in the model were evaluated. Methods . Patients completed measures of cancer clinical trial knowledge, attitudinal barriers, self-efficacy, and preparedness. Structural equation modeling (SEM) was conducted to evaluate whether self-efficacy mediated the association between knowledge and barriers with preparedness. Results . The SEM explained 26% of the variance in cancer clinical trial preparedness. Self-efficacy mediated the associations between attitudinal barriers and preparedness, but self-efficacy did not mediate the knowledge-preparedness relationship. Conclusions . Findings partially support the Ottawa Decision Support Framework and suggest that assessing patients' level of self-efficacy may be just as important as evaluating their knowledge and attitudes about cancer clinical trials.